KAJIAN EKOLOGI JENIS ALGA LAUT BAGI KEHIDUPAN ORGANISME DI ZONA INTERTIDAL PERAIRAN PANTAI KECAMATAN SALAHUTU PULAU AMBON - Tuaputty, Hasan; Latupeirissa, Louvenska Nona; Arini, Ine (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: The coastal waters in the intertidal zone of Tulehu Village, Salahutu District,Ambon Island are a good habitat for the growth of various types of macroalgae which ecologicallyhave an important role for the sustainability of various types of marine biota, because the growthof various macroalgae is very fast with various thallus, allowing an ecosystem to form as a placeto live. live various marine biota.Methods: This research is a descriptive study using sampling techniques for types of Algae bysurvey in the intertidal zone of coastal waters in Tulehu Village, Ambon Island, Salahutu District,Central Maluku Regency. The Algae sampling process was carried out during the tides from January 6 to January 20 2024. . This research is a descriptive study using sampling techniques for types of Algae by survey in the intertidal zone of coastal waters in Tulehu Village, AmbonIsland, Salahutu District, Central Maluku Regency.Results: The findings of marine macroalgae in the Intertidal Zone include Chaetomorpha crassa,Achanthopora muscoides, Gracilaria arcuate, Valonia fastigiata, Ulva lactuca, Sargassumcrassifolium.Conclusion: The macroalgae found in the intertidal zone of the coastal waters of Tulehu Villageon Ambon Island are 6 types of macroalgae, Chaetomorpha crassa, Achanthopora muscoides,Gracilaria arcuate, Valonia fastigiata, Ulva lactuca, Sargassum crassifolium. Ulva lactuca, brownmacroalgae species Achanthopora muscoides, Gracilaria arcuate and red macroalgae speciesSargassum crassifolium, each type of macroalgae has a different substrate according to thesubstrate conditions and the presence of different environmental factors.